2018
DOI: 10.15405/epsbs.2018.07.69
|View full text |Cite
|
Sign up to set email alerts
|

Gender Characteristics Of Junior Adolescents’ Personal Traits

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…To assess the relationships and grouping of psycho diagnostic data, correlation and factor analysis as traditional methods were used, which, when dividing respondents by gender, allows assessing the gender differences of the psychological characteristics links [14]. Varimax normalized method for the factor load matrix rotation was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the relationships and grouping of psycho diagnostic data, correlation and factor analysis as traditional methods were used, which, when dividing respondents by gender, allows assessing the gender differences of the psychological characteristics links [14]. Varimax normalized method for the factor load matrix rotation was used.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the research on gender features of intelligence, emotional sphere and personal characteristics (in particular, children's selfesteem [13]) presented in the Russian psychological literature is devoted to the problem of determining these features by cultural and social context, including in preschool age [14,15]. According To L. I. Bozhovich, the correct formation of self-esteem is one of the most important factors in the development of a child's personality.…”
Section: Introductionmentioning
confidence: 99%
“…It, in one way or another, manifests itself for all groups of students, allocated on the basis of gender or IQ level. Experimentally observed gender heterochrony in personal developmentfor the girls, the signs of age-related crisis occur for six months or a year earlier than boys, the redistribution of the relations of personality traits for them is more pronounced, also the signs of emotional distress during the crisis (Slavutskaya, Nikolaev, Ivanova, & Yusupov, 2018). In the analysis of psycho diagnostic data of students with different levels of IQ found that for children with higher intellectual performance transition period proceeds more smoothly in terms of quantitative and qualitative changes in cross-functional relationships of psychological characteristics.…”
Section: Girlsmentioning
confidence: 93%